Penguatan Kompetensi Penyuluh Anti Korupsi Bagi Guru Mata Pelajaran PPKN SMK Se Kabupaten Pemalang - Natal Kristiono; Erisandi Arditama; Wahyu Beny Mukti S; Rudi Salam; Hanik Latifah; Indri Astuti; Amalya Adya Prastiwi; Sa’ya rosada Al Firdaus; Meike Dwi Novita (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Education has the function of instilling, developing, and implementing rational values, regularity, diligence, and productive attitudes which in turn are able to bring about humans who have noble character, are devoted to God Almighty, and have human values. Pancasila and Citizenship Education or what is more often called PPKn is one of the subjects that must be given to students in order to form good citizens, loyal to Pancasila and the 1945 Constitution. The aim of this activity is to increase the competency of PPKn teachers in the field of Anti-Corruption Education, eradicating corruption through more effective and systematic educational strategies through students and teachers in anti-corruption outreach efforts. The implementation method is training which aims to increase understanding of the dangers of criminal acts of corruption and strengthen commitment as an extension of the eradication of corruption, followed by training in the form of mentoring prospective Anti-Corruption Counselors. It is hoped that the results of this activity will be that participants will later become anti-corruption educators, which requires a strong will and determination to lead the anti-corruption movement, namely perfection in conveying basic anti-corruption information and integrity. willing to have anti-corruption teacher qualifications